Defining Enhanced Recovery Pathway with or without Liposomal Bupivacaine in DIEP Flap Breast Reconstruction. Issue 5 (November 2021) - Haddock, Nicholas T.; Garza, Ricardo; Boyle, Carolyn E.; Liu, Yulun; Teotia, Sumeet S.
Abstract : Background: Enhanced recovery after surgery (ERAS) includes multiple interventions that have yielded positive outcomes in a number of surgical fields. The authors evaluated whether an ERAS protocol and the subsequent addition of liposomal bupivacaine affect patient outcomes specifically in deep inferior epigastric perforator (DIEP) flap breast reconstruction. Methods: All patients treated with DIEP flaps from January of 2016 to December of 2019 were reviewed retrospectively. The ERAS protocol was implemented midway through 2017; halfway through 2018, intraoperative transversus abdominis plane blocks with liposomal bupivacaine were added to the protocol. Such interventions allowed for comparison of three patient groups: before ERAS, during ERAS, and after ERAS plus liposomal bupivacaine. Primary outcomes observed were postoperative opioid consumption and length of stay. The p values were obtained using the Wilcoxon test for pairwise comparisons. Results: After adjusting for ERAS group compliance, 216 patients were analyzed. The pre-ERAS group was composed of 67 patients, the ERAS group was composed of 69 patients, and the ERAS plus liposomal bupivacaine group was composed of 80 patients. Postoperative opioid consumption was reduced when comparing the pre-ERAS and ERAS groups (from 275.7 oral morphine equivalents to 146.7 oral morphine equivalents; p < 0.0001), and also reduced with the addition of liposomal bupivacaine (115.3 oral morphine equivalents; p = 0.016). Furthermore, hospital length of stay was decreased from 3.6 days in the pre-ERAS group to 3.2 days ( p = 0.0029) in the ERAS group, and to 2.6 days ( p < 0.0001) in the ERAS group plus liposomal bupivacaine groups. Conclusions: Enhanced recovery after surgery protocols decrease postoperative opioid consumption and hospital length of stay in DIEP flap breast reconstruction. The addition of liposomal bupivacaine further strengthens the impact of the protocol. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.